Low-Frequency Ultrasound Assisted in Improvement in Cell Development and Production of Parasporal Crystals from Bacillus thuringiensis HD1 - Sufen Cui; Kaihui Shen; Shiqi Xiong; Xiao Li; Yue Wang; Xueqing Geng; Yujie Lu (Insects)
Bacillus thuringiensis is widely utilized as a microbial insecticide due to its production of parasporal crystals during the spore-forming stage. However, lower fermentation efficiency coupled with elevated production costs limit its broad application. Low-frequency ultrasound (LFU) has been employed in the fermentation industry to enhance microbial growth and metabolism. In this study, the effect of LFU on the growth of B. thuringiensis HD1 and the yields of parasporal crystals was investigated. The maximum biomass accumulation of Bacillus thuringiensis and parasporal crystal production yield were achieved following low-frequency ultrasonic (LFU) treatment applied during the logarithmic growth phase (18 h of cultivation) under optimized parameters: a frequency of 40 kHz, a power output of 176 W, and an irradiation duration of 45 min. Under optimal conditions, LFU significantly increased the cell membrane permeability and secretory inositol, favoring cell growth and parasporal crystal production. FESEM/CLSM and TEM analyses visually displayed the changes in cell morphology. In addition, the germination rate of spores was increased after LFU treatment, which further confirmed the positive effect of LFU on the growth of B. thuringiensis. Compared to the control, parasporal crystals harvested under LFU exhibited significant modifications in their physicochemical characteristics; the particle size increased, the surface electronegativity intensified, and there was a morphological transition from spherical to cubic geometry. Importantly, the parasporal crystals exhibited strong insecticidal activity against S. zeamais adults, a typical stored-product insect pest, with an LC50 of 10.795 mg/g on day 14 and a Kt50 of 4.855 days at a concentration of 30 mg/g. These findings will provide new insights into the product development and application of B. thuringiensis in the future.